Interval oscillation criteria for a forced second order nonlinear ordinary differential equation - Li, Wan-Tong; Agarwal, Ravi P. (Applicable analysis, 2000)
New oscilation criteria are established for the nonlinear differential equation that are different from most kown ones in the sense that they are based on the information only on a sequence of subintervals of (t 0 ∞),rather than on the whole half-line. In particular, several examples that dwell upon the importance of our results are also included.